Inserção das propriedades familiares na cadeia da madeira: um diagnóstico do Sul do Brasil - Biali, Leonardo Job (2016)
Except for the local structures such as the market of firewood and small sawmills, the Brazilian forest complex is supplied almost entirely by wood from medium and large enterprises. This work had the assumption that family lands can also be a competitive source of forest products for wood production chain. To support this hypothesis a diagnosis of forest production on family lands from southern Brazil was carried out, and was based on two sample groups. In the first group were evaluated both the productive structure of the lands and families, the relationship of the rural producers with foresting and the use of wood, and the existing forestry base. In the second group, that comprised the rural lands that have implemented foresting, it was assessed the current state of forestry. Small lands possess area to expand the forest production without impairing the productive activities that have already been undertaken, but present restrictions on labor availability. Family farmers have a wide tradition in forest cultivation, however it does not reflect in a deep technical knowledge about this subject. In addition, the contribution of the technical assistance institutions on forestry is deficient. The wood consumption is significant in lands due its use for drying agricultural products. Therefore, the lands can not manage to supply itself and need to turn to the market. Besides the most of the lands have forestation, in many cases these forests present low quality and multiple cutting cycles. Family forests have increment consistent with the average of the forest sector, but this growth is a result of the employment of high densities. The low quality displayed by these forests is repeated in the new plantations, which are quite dense and present deficiencies in the practices of implementation of silviculture resulting in a high mortality rate. To these lands insert themselves into the market, it is necessary an effective performance of the assistance institutions in order to reverse this technological gap frame. It is also essential to increase the production capacity both by the expansion of the forest base and by the increase of the productivity in the areas that have been forested. The diagnosis herein presented indicates that the current models of foment are not suitable to the reality of the small rural lands. Due the high demand for wood, it is necessary that producers have greater autonomy over the offered products, and that the incentive of forest production should be mainly based on a guarantee of the access to the market, more than in the funding of production.